Broadening Anti-Consumption Research: A History of Right-Wing Prohibitions, Boycotts, and Resistance to Sustainability. (December 2021) - Witkowski, Terrence H.
Anti-consumption scholarship has been ideologically one-sided. It has established a research domain aligned with projects favored by the global political left, such as being environmentally sustainable, consuming ethically, and resisting corporate capitalism, while overlooking strains of anti-consumption thought and action driven by conservative interests. It has advanced knowledge of individuals, their reasoning, and market behavior patterns in the here and now, but has neglected the state-sponsored and temporal dimensions of anti-consumption phenomena. This article seeks to redress this imbalance and broaden the field through a historical counternarrative illustrating right-wing prohibitions, boycotts of media content, brands, and companies, and, most recently, resistance to sustainable consumption. The different interests served, effects on consumption behavior, and market and societal impacts of these anti-consumption efforts in the American experience are analyzed. Implications for the domain of anti-consumption and macromarketing research and opportunities for potential global study are discussed.